(untitled) (Italian Journal of Public Health, 2008)
Background: The objective of this study was to evaluate in a sample of parents living in an inner-city area of Palermo, Italy, the perception of weight excess as a problem in childhood and the awareness about the role of physical activity, beliefs about contributors and parties having responsibility in counteracting the obesity crisis. Methods: A cross-sectional survey was performed on a convenience sample of parents of 6-13 year-old children who attended grades 1, 3 and 5 of primary and grades 1 and 3 of secondary public schools, respectively. Thirteen schools were selected in an inner urban district of Palermo, Italy, this district being characterized by having a population of low to medium income residents. Parents were asked to come to the school and participate in the investigation. The survey was administered in the spring of 2006. After a descriptive analysis, role of specific demographic and social characteristics – education, gender, age class and BMI - of respondents was assessed by univariate and multivariate logistic regression analysis. Results: Three hundred eleven parents completed the questionnaire. Eighty-three percent believed that being obese in childhood is a serious health hazard, but one third still interpreted the child’s weight excess as an expression of health. The most significant contributors to childhood obesity were thought to be junk food and beverages (78.0%) and fast food (63.2%), followed by lack of exercise in school curriculum (48.7%). Beliefs about responsibilities for combating childhood obesity significantly varied according to education level. Conclusions: Public support for environmental changes could more effectively rise with the increasing public awareness that many interrelated obesogenic factors in the modern environment are playing a key role.